Amnesty for crime in international law and practice - O'Shea, Andreas (Kluwer Law International, 2002)
A comprehensive study of the relationship between municipal amnesty laws and developing principles of international criminal law. This book pursues a path towards defining criteria for reconciling these two delicate fields of transitional justice.